ANALISIS BREAK EVEN POINT (BEP) SEBAGAI ALAT PERENCANAAN LABA PADA UD. DAPUR SEHATI DESA SEMIRING KABUPATEN SITUBONDO - Anik Sudarismiati; Zainal Anshory (Growth, 2018)
Profit planning needed in a company needs all types of production activities not in vain, and with this analytical method the company can minimize costs that may be needed. The measure that is often bought for success is not the management of a company is the profit obtained by the company. Income by three factors, namely product selling prices, costs and sales volume. This research was conducted with the aim of (1) Find the BEP level obtained by UD. Dapur Sehati in 2016. (2) Know the sales plan at UD. Dapur Sehati in 2017 and 2018. (3) Find out the profit plan you want to achieve UD. Dapur Sehati in 2017 and 2018. This research was conducted at UD. Dapur Sehati Semiring Village, Situbondo Regency. Data obtained by using documentation techniques, interviews, and literature. Data analysis uses the Break Even Point formula, Margin of Safety, Margin, quadratrate method, sales forecast, and minimal sales. UD. Dapur Sehati is a company that manufactures various processed fish, one of which is shredded tuna. The results of the analysis are as follows: (1) BEP for tuna abon products is 6,548 units with a nominal value of Rp 163,710,358. (2) The Safety Margin of tuna shredded products is 69%. (3) The margin of donating tuna shredded products is Rp. 238,266,250, and the approved margin ratio is 48%. (4) Based on UD sales forecast. Dapur Sehati will be able to reach sales volume of 21,184 pcs in 2017 with a value of Rp.529,600,000 and sales forecast for 2018 UD. Dapur Sehati will be able to reach sales volumes of 23,608 pcs with a value of Rp.590,200,000. (5) in 2017 UD's profit plan. Dapur Sehati for Rp. 175,802,667. While in 2018 UD's profit plan. Dapur Sehati is Rp. 204,890,667.